PENGARUH EARNINGS MANAGEMENT DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR KEPEMILIKAN SEBAGAI MODERATING VARIABLE PADA PERUSAHAAN KELOMPOK LQ 45 DI BEI TAHUN 2013-2016 - Nurhanimah Nurhanimah; Rita Anugerah; Vince Ratnawati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
The purpose of this study was to determine the effect of earnings management and tax avoidance on firm value with ownership structure as a moderating variable. This research was conducted on companies registered in the LQ 45 index for the period 2013-2016 with a purposive sampling technique. Data analysis technique using WarpPLS version 5.0. The results show that earnings management affects the value of the company, whereas tax avoidance does not affect the value of the company. The researcher also found managerial ownership does not moderate the relationship between earnings management and tax avoidance on firm value. Institutional ownership moderates the earnings management on firm value but does not moderate the relationship between tax avoidance on firm value.